Proceedings of the National Seminar on The Legal Regime of Sustainable Land Use and Environmental Development : policies and trends, 9th August 2003, Banquet Hall, Rectory, International Islamic University, Malaysia, Gombak, Kuala Lumpur - National Seminar on The Legal Regime of Sustainable Land Use and Environmental Development (2003 : International Islamic University, Malaysia); Land Tenure and Environmental Management Unit (Kuala Lumpur : International Islamic University Malaysia, 2003)
28